2013
DOI: 10.14260/jemds/377
|View full text |Cite
|
Sign up to set email alerts
|

Study of Urinary Isolates With Reference to Extended Spectrum Beta Lactamases Detection and Antibiogram

Abstract: BACKGROUND:Extended spectrum beta lactamases continue to be major problem in clinical setups world over, conferring resistance to extended spectrum cephalosporins and are associated with significant morbidity and mortality. Urinary tract infections (UTIs) are one of the most common infectious diseases encountered in the clinical practice. Extended spectrum beta lactamases (ESBLs) production in gram negative bacteria, have emerged as a major problem in hospitalized as well as community based patients. ESBLs pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A significant increase in the incidence of infections associated with extended-spectrum beta-lactamase (ESBL) producing organisms has been observed throughout the world (Gupta, 2007;Fatemeh et al, 2012;Abhijit et al, 2013;Majda et al, 2013;Meeta et al, 2013 andRupinder et al, 2013). These types of organisms have different alleles such as SHV-1 (named after the Sulfhydryl-variable active site), CTX-M (which preferentially hydrolyze cefotaxime over ceftazidime and also cefepime with high efficiency), TEM-1 (designated Temoniera) and blaCTX-M (which are well represented in many different genera of the family Enterobacteriaceae and Pseudomonas aeruginosa).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in the incidence of infections associated with extended-spectrum beta-lactamase (ESBL) producing organisms has been observed throughout the world (Gupta, 2007;Fatemeh et al, 2012;Abhijit et al, 2013;Majda et al, 2013;Meeta et al, 2013 andRupinder et al, 2013). These types of organisms have different alleles such as SHV-1 (named after the Sulfhydryl-variable active site), CTX-M (which preferentially hydrolyze cefotaxime over ceftazidime and also cefepime with high efficiency), TEM-1 (designated Temoniera) and blaCTX-M (which are well represented in many different genera of the family Enterobacteriaceae and Pseudomonas aeruginosa).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms have universal dissemination and are readily recovered from various samples including both living (Fatemeh et al, 2012;Abhijit et al, 2013;Popoola et al,2019) and non-living samples (Thomas et al,2015). Their presence in almost every conceivable environment is well reported (Fatemeh et al, 2012;Abhijit et al, 2013;Popoola et al,2019), while some recovery from toilet seats, sinks and toilet environments have also been documented (Balogun et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment against these multidrug-resistant bacteria is of profound scientific concern. Recent ongoing studies showed a substantial change in the cases of ESBL-related diseases notified across the world [ 3 ]. Recently, there has been a hypothetical move in the subtraction of probable antibacterials.…”
Section: Introductionmentioning
confidence: 99%